Primary care and referring physician perspectives on non-alcoholic fatty liver disease management: a nationwide survey. (September 2021) - Saeed, Naba; Glass, Lisa M.; Habbal, Heba; Mahmood, Asad; Sengstock, David; Saini, Sameer D.; Tincopa, Monica A.
Introduction: The optimal approach to screening and risk stratification for non-alcoholic fatty liver disease is challenging given disease burden and variable progression. The aim of this study was to assess primary care physician and referring physician practice patterns regarding non-alcoholic fatty liver disease. Methods: An anonymous nationwide survey was administered to primary care physicians, endocrinologists, and cardiologists in a: (1) tertiary academic hospital, (2) community hospital, and (3) the American College of Physicians Insider Panel. Survey domains assessed non-alcoholic fatty liver disease knowledge, recommendations for screening, risk stratification, treatment, and referral patterns. Results: A total of 440 providers completed the survey (35.2% completion rate; N  = 82 academic hospital, N  = 21 community hospital, N  = 337 American College of Physicians). Half were male (51.7%), 78% from internal medicine, with 5% subspecialists. Providers were knowledgeable regarding prevalence and risk factors for non-alcoholic fatty liver disease. 58% would support screening for non-alcoholic fatty liver disease and used liver enzymes to do so. Only 22.5% used serum biomarkers and 23% used transient elastography for risk stratification. Primary reason for referral was advanced fibrosis/cirrhosis. 80% reported barriers to treating non-alcoholic fatty liver disease. There was no consistent diet recommended. Conclusion: In this nationwide survey, we demonstrated that while overall disease knowledge was good, there was an important disconnect between current guidelines and real-world clinical practice. There is also significant heterogeneity in practice patterns for first-line therapy of non-alcoholic fatty liver disease and the majority of provider's report barriers to treating non-alcoholic fatty liver disease. These findings highlight the potential role for reevaluating screening and risk stratification recommendations in primary care to better align with needs in that setting.